Clinical characteristics and treatment of 50 cases of Blau syndrome in Japan confirmed by genetic analysis of the NOD2 mutation. Issue 11 (9th July 2020) - Matsuda, Tomoko; Kambe, Naotomo; Ueki, Yoko; Kanazawa, Nobuo; Izawa, Kazushi; Honda, Yoshitaka; Kawakami, Atsushi; Takei, Syuji; Tonomura, Kyoko; Inoue, Masami; Kobayashi, Hiroko; Okafuji, Ikuo; et al.
Abstract : Objectives: To collect clinical information and NOD2 mutation data on patients with Blau syndrome and to evaluate their prognosis. Methods: Fifty patients with NOD2 mutations were analysed. The activity of each NOD2 mutant was evaluated in HEK293 cells by reporter assay. Clinical information was collected from medical records through the attending physicians. Results: The study population comprised 26 males and 24 females aged 0–61 years. Thirty-two cases were sporadic, and 18 were familial from 9 unrelated families. Fifteen different mutations in NOD2 were identified, including 2 novel mutations (p.W490S and D512V); all showed spontaneous nuclear factor kappa B activation, and the most common mutation was p.R334W. Twenty-six patients had fever at relatively early timepoints in the disease course. Forty-three of 47 patients had a skin rash. The onset of disease in 9 patients was recognised after BCG vaccination. Forty-five of 49 patients had joint lesions. Thirty-eight of 50 patients had ocular symptoms, 7 of which resulted in blindness. After the diagnosis of Blau syndrome, 26 patients were treated with biologics; all were antitumour necrosis factor agents. Only 3 patients were treated with biologics alone; the others received a biologic in combination with methotrexate and/or prednisolone. None of the patients who became blind received biologic treatment. Conclusions: In patients with Blau syndrome, severe joint contractures and blindness may occur if diagnosis and appropriate treatment are delayed. Early treatment with a biologic agent may improve the prognosis.